Strategi Peningkatan Mutu Pendidikan Melalui Analisis SWOT - Dana Luwihta, Aisyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to: 1) Understand how STAI Hasan Jufri improves the quality of education through SWOT analysis, 2) Identify the follow-up position of STAI Hasan Jufri Bawean in the SWOT Analysis. The research in this study uses a qualitative approach with research subjects being the leadership and heads of departments. The research goes through four stages, with the first stage involving data collection through interviews, observations, and documentation to gather data on internal factors (strengths and weaknesses) and external factors (opportunities and threats) as data acquisition. The second stage involves data reduction using EFE and IFE matrices. The third stage presents the data, and the final stage involves concluding. The results of the research indicate that: 1) STAI Hasan Jufri Bawean has not fully utilized SWOT Analysis theory in its strategic analysis, 2). STAI Hasan Jufri Bawean is positioned in Quadrant I with a strength of 0,07 and a threat of 0,03, and the strategy implemented is an aggressive strategy, which results in an appropriate reference for improving the quality of education at STAI Hasan Jufri Bawean.